The Effectiveness of Combination of Back Massage and Deep Breathing Exercises on Changes in Hemodynamic Status (SpO2) Patients of Congestive Heart Failure - Nabella Ayu Jeihan Fadhila; Hotma Rumahorbo; Sudirman Sudirman (Faculty of Nursing, Universitas Jember, 2023)
In Indonesia, 25% of deaths are caused by heart defects. 229,696 people, or about 0.13%, were heart failure patients. The main problem that occurs in heart failure is hemodynamic changes. If not treated quickly and appropriately, hemodynamic disorders will result in multiple organ failures. Back massage and deep breathing exercise is a combination of non-pharmacological interventions whose effectiveness is not yet known in improving hemodynamic disorders in CHF patients. To determine the effectiveness of the combination of back massage and deep breathing exercise on changes in the hemodynamic status of patients with congestive heart failure. This type of research is quantitative with a true experimental design, a pre-post test design, and a control group. The sampling technique used is simple random sampling. Data analysis used repeated measure ANOVA, Friedman test, independent t-test, and Mann Whitney. The combination of back massage and deep breathing exercise is given for 3 days with a duration of 15 minutes, effectively increasing oxygen saturation (Mean±SD 98.20±0.616 =1.05 p=0.000). Giving a combination of back massage and deep breathing exercises can improve the hemodynamic status of patients with congestive heart failure. The results of this study can be used as an alternative intervention in improving the hemodynamic status and providing other pharmacological and non-pharmacological therapies.